An Auction-Based Scheduling Approach for Minimizing Latency in Fog Computing Using 5G Infrastructure - Fahmy, Ahmed (2020)
A Master of Science thesis in Computer Engineering by Ahmed Fahmy entitled, “An Auction-Based Scheduling Approach for Minimizing Latency in Fog Computing Using 5G Infrastructure”, submitted in February 2020. Thesis advisor is Dr. Raafat Aburukba and thesis co-advisor is Dr. Taha Landolsi. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).